La emigración de argentinos con doble nacionalidad: Una inmigración invisibilizada desde Misiones a Suiza y Alemania - Gallero, María Cecilia (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The citizenship of a country brings many benefits to inhabitants, but above all to those who are immigrants. The objective of this article is to reflect on Argentine citizens with dual nationality, who due to the economic or political situation decided to emigrate from the province of Misiones to Switzerland or Germany. The concept of citizenship is often thought of as something simple, but when describing the plot of elements interrelate individual instance with the political system, the concept becomes more complex. In the right to Argentine citizenship, the ius solis prevails: being born on this land grants an inalienable nationality. These rights intrinsic to the ius solis or the “nationalization” of foreigners, are contrasted with countries granting citizenship by the ius sanguinis. The tension generated in the descendants of immigrants between the ius sanguinis of the nation of origin and the ius solis of Argentina is reflected in this article in four sections: the first is a brief contextualization of the German-Brazilian, German and Swiss migration to Misiones, in the second is exposed the difference between these nationalities-citizenships; to continue with some cases that have been traced along different investigations about Argentines who emigrated to Switzerland or Germany. Finally, we come to some reflections on transnational citizenship in relation to dual citizenship.